Chaucer - Preston, Raymond (Sheed and Ward, 1952)
The aim of this book is to interpret the work of Chaucer to the modern reader. This for a twofold reason: the modern reader does need help in order to understand Chaucher, and Chaucer is worth the effort of understanding.